2016
DOI: 10.1016/j.calphad.2015.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic modeling of Al–Co–Cr, Al–Co–Ni, Co–Cr–Ni ternary systems towards a description for Al–Co–Cr–Ni

Abstract: the modeling of the subsystems, especially Al-Co-Ni and Co-Cr-Ni, necessary in building a coherent Al-Co-Cr-Ni quaternary description. Some modifications are made in the description of the Al-Co-Cr [5] system and are discussed in detail later in the manuscript. The quaternary Al-Co-Cr-Ni system is studied in a separate publication [8].While B2 (β, , simple cubic type) and fcc-A1 (γ, , disordered f.c.c.) are the desired phases in MCrAlY coatings, all other phases must be modeled to give an accurate overall desc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 65 publications
(29 citation statements)
references
References 75 publications
0
28
0
Order By: Relevance
“…All phase equilibrium calculations were done for T = 1100 • C, using the NIST database [28] in Thermo-Calc [29]. The later use of CRALDAD, a more recent database specifically developed for the Al-Co-Cr-Ni system [30,31], showed that the alloys were in fact slightly off the tie-lines; nevertheless, the principle of independently varying phase fractions and phase compositions is still qualitatively valid. For clarity of reading, the alloys will be referred to using their β fraction (vol.…”
Section: Materials and Experimentsmentioning
confidence: 99%
“…All phase equilibrium calculations were done for T = 1100 • C, using the NIST database [28] in Thermo-Calc [29]. The later use of CRALDAD, a more recent database specifically developed for the Al-Co-Cr-Ni system [30,31], showed that the alloys were in fact slightly off the tie-lines; nevertheless, the principle of independently varying phase fractions and phase compositions is still qualitatively valid. For clarity of reading, the alloys will be referred to using their β fraction (vol.…”
Section: Materials and Experimentsmentioning
confidence: 99%
“…As a test of the latter aspect, concentration profiles in the single-phase γ alloys Ni-28Co-19Cr-11Al-0.1Y and Ni-33Co-35Cr-7Al-0.1Y oxidized with and without deposit were simulated in Dictra, using the experimentally measured interfacial and bulk concentrations as boundary conditions. The diffusivities were computed from the CRALDAD thermodynamic database, which was optimized for high Co and Cr levels in the NiCoCrAl system [17,18], and the MobNi1 [19] and NIST Ni Superalloy [20] mobility databases (both gave similar results). In all cases, the simulated profiles matched the experimental profiles less well than when using an effective D a Al (the computedD Ni Al,Al values were higher than our D a Al values by a factor of 10).…”
Section: Future Considerationsmentioning
confidence: 99%
“…For Al-Co-Cr system neither a liquidus projection nor a minimum eutectic composition is reported. However, Liu et al [33] modeled the isothermal section of Al-Co-Cr system at 1300 °C, and from the isothermal section, the boundaries of the two phase region γ+B2 can be obtained ( Figure 1e). According to the boundaries of the two phase region γ+B2 at 1300 °C, the eutectic line could be predicted which is shown in Figure 1e.…”
Section: Model Developmentmentioning
confidence: 99%